TINJAUAN SISTEMATIK FARMAKOLOGI DAN TOKSISITAS TANAMAN BANDOTAN (Ageratum conyzoides L.) - Sukmawan, Yedy Purwandi (LPPM Universitas Bakti Tunas Husada, 2024)
Ageratum conyzoides is a plant renowned for its medicinal properties since ancient times. However, a thorough systematic review of the pharmacology and toxicity of this plant is still limited and without an explanation of the study stage, such as preclinical or clinical. A literature search was performed on various databases, including Pubmed, Cochrane, Science Direct, and Google Scholar, using specific keywords such as Ageratum conyzoides, Pharmacology, Safety, and Toxicity. The search yielded various pharmacological activities. The clinical stage of the pharmacological study is only for anti-benign prostate hyperplasia activity. However, the activity of anti-microbial, anti-poison, analgesic-antiinflammatory, hemostatic, wound healing, radioprotective, cardioprotective, vasorelaxant, spasmolytic, hematopoietic, anti-hyperglycemic, gastroprotective, insecticidal, hepatoprotective, and anticonvulsant are still in preclinical stages. In toxicity study, In general extract preparations of A.conyzoides is considered safe, however there are concerns about side effects to liver, kidney, hematological, and heart. A. conyzoides has a broad range of pharmacological activities, but there are concerns regarding its safety profiles.